2010
DOI: 10.1007/s11032-010-9497-y
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of an intermediate VRNH1 allele in barley (Hordeum vulgare L.) leads to reduced vernalization requirement without affecting freezing tolerance

Abstract: The process of vernalization is mainly controlled by two genes in winter barley (Hordeum vulgare L.), VRNH1 and VRNH2. A recessive allele at VRNH1 and a dominant allele at VRNH2 must be present to induce a vernalization requirement. In addition, this process is usually associated with greater low-temperature tolerance.Spanish barleys originated in areas with mild winters and display a reduced vernalization requirement compared with standard winter cultivars. The objective of this study was to investigate the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The first intron is similar to the HvVRN1-4 allele of Hemming et al (2009) but it contains an additional 7-bp deletion (GenBank accession DQ492705). Under controlled conditions it behaves like the Spanish landrace SBCC058 (Casao et al 2011b). The RIL population was developed in Lleida and, therefore, its rather warm temperatures may have shifted the population towards an overrepresentation of the Orria allele at VrnH1, resulting in the skewed allelic frequencies observed in the linkage group 5H.3.…”
Section: Discussionmentioning
confidence: 99%
“…The first intron is similar to the HvVRN1-4 allele of Hemming et al (2009) but it contains an additional 7-bp deletion (GenBank accession DQ492705). Under controlled conditions it behaves like the Spanish landrace SBCC058 (Casao et al 2011b). The RIL population was developed in Lleida and, therefore, its rather warm temperatures may have shifted the population towards an overrepresentation of the Orria allele at VrnH1, resulting in the skewed allelic frequencies observed in the linkage group 5H.3.…”
Section: Discussionmentioning
confidence: 99%
“…Also, care should be taken to ascertain the agronomic effects of possible adaptation syndromes that have been selected for in the landraces over time, affecting at the genes of the vernalization and photoperiod pathways (Casao et al. ,b). Ongoing work using genome‐wide association mapping and linkage mapping approaches with biparental populations derived from the best Spanish lines (Silvar et al.…”
Section: Discussionmentioning
confidence: 99%
“…Trevaskis et al. (2006) and Casao et al. (2011) have shown that in winter barley, Vrn‐H1 only indirectly controls HvFT levels through the down‐regulation of Vrn‐H2 , which is a repressor of HvFT1 .…”
Section: Discussionmentioning
confidence: 99%